Human mitochondrial NDUFS3 protein bearing leigh syndrome mutation is more prone to aggregation than its wild-type - Jaokar, Tulika M.; Patil, Deepak P.; Shouche, Yogesh S.; Gaikwad, Sushama M.; Suresh, C. G. (Biochimie, 2013)
NDUFS3 is an integral subunit of the Q module of the mitochondrial respiratory Complex-I. The combined mutation (T145I + R199W) in the subunit is reported to cause optic atrophy and Leigh syndrome accompanied by severe Complex-I deficiency. In the present study, we have cloned and overexpressed the human NDUFS3 subunit and its double mutant in a soluble form in Escherichia coli. The wild-type (w-t) and mutant proteins were purified to homogeneity through a serial two-step chromatographic purification procedure of anion exchange followed by size exclusion chromatography. The integrity and purity of the purified proteins was confirmed by Western blot analysis and MALDI-TOF/TOF. The conformational transitions of the purified subunits were studied through steady state as well as time resolved fluorescence and CD spectroscopy under various denaturing conditions. The mutant protein showed altered polarity around tryptophan residues, changed quenching parameters and also noticeably altered secondary and tertiary structure compared to the w-t protein. Mutant also exhibited a higher tendency than the w-t protein for aggregation which was examined using fluorescent (Thioflavin-T) and spectroscopic (Congo red) dye binding techniques. The pH stability of the w-t and mutant proteins varied at extreme acidic pH and the molten globule like structure of w-t at pH1 was absent in case of the mutant protein. Both the w-t and mutant proteins showed multi-step thermal and Gdn-HCI induced unfolding. Thus, the results provide insight into the alterations of NDUFS3 protein structure caused by the mutations, affecting the overall integrity of the protein and finally leading to disruption of Complex-I assembly. (C) 2013 Elsevier Masson SAS. All rights reserved.
Keywords: Aggregation Fluorescence lifetime; Complex-I; Leigh syndrome; NDUFS3

Solution and in silico studies on the recombinant lectin from Cicer arietinum seeds - Wakankar, Madhurima S.; Krishnasastry, Musti V.; Jaokar, Tulika M.; Patel, Krunal A.; Gaikwad, Sushama M. (International Journal of Biological Macromolecules, 2013)
The Cicer arietinum seed lectin was cloned and expressed in Escherichia coli and purified in active form. Conformational characterization of the recombinant lectin (rCAL) was performed using biophysical and bioinformatics tools. Thermal denaturation of rCAL caused rapid secondary structural rearrangements above 50 degrees C and transient exposure of hydrophobic residues at 55 degrees C, leading to aggregation. Treatment of rCAL with GdnHCl resulted in unfolding followed by dissociation of the dimer. The single tryptophan in rCAL present on the surface of the protein is surrounded by hydrophobic and acidic amino acids and exists as different conformers. The experimental observations correlated well with the structural information revealed from the homology model of rCAL. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Aggregation; BL21-CodonPlus (DE3)-RIL cells; Cicer lectin; Homology model; Steady-state and time resolved fluorescence; Unfolding